Reimagining the journey – expanding the History curriculum to teach for depth of understanding in the FET Phase (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
While the NSC CAPS does prescribe topics to be taught in the FET Phase of schooling, it does not restrict an educator from teaching additional topics or extending topics. It will be argued that there is a necessity for learners to develop a deeper understanding of prescribed CAPS topics in Grade 12, which includes the Research Task. It is suggested additional topics in the Grade 10 curriculum, such as aspects of the “American War of Independence” and the “Abolition of Slavery” in both the British Empire and United States of America need to be taught, and the sub-topic in Grade 11 on Pan-Africanism needs to be extended for this purpose. In asking why history educators do not extend aspects of the curriculum, this paper explains what and how expanding the history curriculum should be undertaken through the three-year programme of the FET Phase. More importantly, it is suggested this approach provides learners with insights to engage and contribute to current debates in South Africa and the world at large. The paper will conclude with recommendations on how this in-depth understanding can be incorporated into the curriculum.
Keywords: FET Phase; Additional Topics; Depth of Understanding; Background Context; Educator; Pan Africanism; History; Current Debates